2007
DOI: 10.1542/peds.2007-0114
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Delivery-Room Respiratory Management in Very Preterm Infants

Abstract: A sustained inflation followed by early nasal continuous positive airway pressure, delivered through a nasopharyngeal tube, is a more efficient strategy than repeated manual inflations with a self-inflating bag and mask followed by nasal continuous positive airway pressure on admission to the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
161
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(172 citation statements)
references
References 43 publications
10
161
0
1
Order By: Relevance
“…In our previous trial comparing 2 DR strategies, 21 the interface (nasal tube versus mask) was only one of several differences (T-piece, self-inflating bag, and 1 group receiving an SI) between the 2 strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous trial comparing 2 DR strategies, 21 the interface (nasal tube versus mask) was only one of several differences (T-piece, self-inflating bag, and 1 group receiving an SI) between the 2 strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] The use of a nasal interface in the DR has been studied but in more mature infants 19 using long (sustained) inflation times, 16,20 anatomic face masks as a comparator, 19 and different strategies and manual ventilation devices. 21 A study comparing a nasal interface with a round silicone face mask in the resuscitation of very immature infants, those most at risk of acquired lung injury, has not been performed.…”
mentioning
confidence: 99%
“…Recently, te Pas et al 46 reported results from a randomized, controlled trial of sustained inflation in the delivery room respiratory management of VLBW infants. These authors compared sustained inflation for 10 s at 20 cm H 2 O applied via a nasopharyngeal tube followed by NCPAP vs manual inflations with a self-inflating bag and mask followed by NCPAP in 207 preterm infants.…”
Section: Noninvasive Ventilation Strategiesmentioning
confidence: 99%
“…Preclinical experimental studies of SI have been mixed (5,6,(9)(10)(11)20), with an increase in lung injury reported in some studies (21)(22)(23). Improved short-term respiratory outcomes have been reported in some clinical trials (24,25), although without long-term benefits, and an increased risk of patent ductus arteriosus (19).…”
mentioning
confidence: 99%
“…The role of recruitment maneuvers on subsequent respiratory therapies may also be important. Clinical studies of SI have suggested a reduced need for surfactant replacement following a SI (24)(25)(26). However, in preterm lambs, pretreatment with surfactant improves the lung injury patterns and response to a SI compared with post-SI surfactant (12), suggesting a recruitment maneuver may also influence subsequent respiratory therapies (8).…”
mentioning
confidence: 99%